Non-invasive detection of fibrosis in non-alcoholic fatty liver disease by serum microfibrillar-associated protein 4 and its correlation with FIB-4 and transient elastography - Heba Abdel Rahman Eltony; Gamal Kasem; Radwa Mahmoud Elsharaby; Rehab Badawi; Eman M. Helal (Egyptian Liver Journal)
Abstract Background and study aim The accumulation of macrovesicular hepatic lipids in persons who drink little or no alcohol is called non-alcoholic fatty liver disease (NAFLD), which is a clinicopathological liver condition that involves a range of fatty liver abnormalities from hepatic steatosis to non-alcoholic steatohepatitis, which can evolve to liver fibrosis and advanced cirrhosis that may lead to liver cell failure and, eventually, hepatocellular carcinoma. In this study, we examined fibrosis in NAFLD patients non-invasively by using serum microfibrillar-associated protein 4, and we correlated it with the fibrosis-4 score and transient elastography. Patients and methods This cross-sectional study was conducted on 90 subjects ≥ 18 years. The participants were classified into Group 1 (study group) consisted of 70 patients with NAFLD diagnosed by bright liver on ultrasound, then controlled attenuation parameter determination of liver steatosis > 240 dB/m, and Group 2 (control group) consisted of 20 healthy participants without NAFLD. FIB–4 and NAFLD Fibrosis Score were measured, and MFAP4 was measured by ELISA. Results MFAP4 was significantly higher in NAFLD than in the control. FIB–4, NAFLD fibrosis score, and MFAP4 were significantly higher in the F3 + F4 group compared to the F1 + F2 group. And MFAP4 was positively correlated with FIB–4 and fibrosis grade. Univariate analysis was done to detect the risk factors for increased MFAP4 in NAFLD patients and showed that the increase of weight, body mass index, 2-h postprandial glucose, fibrosis-4, NAFLD Fibrosis Score, fibrosis score and steatosis score by transient elastography were risk factors in those patients. While multivariate analysis found that fibrosis score was the only independent risk factor that increased MFAP4 in those patients. Conclusions According to this study, serum MFAP4 is increased in NAFLD patients and may be used in conjunction with FIB 4 as a biomarker to screen for advanced liver fibrosis and cirrhosis in NAFLD.